The impact of incentive pay on corporate crime - Daniel Herold (Philipps-University Marburg, School of Business and Economics, 2017)
This paper presents a moral hazard model analyzing the agent's incentive to commit corporate crime. The principal can only observe profits which the agent can increase by committing crime or exerting effort. It is shown how different incentive contracts, i.e., thresholdlinear, capped bonus and linear contracts, can be adjusted in order to promote agent's law abiding behavior. Any adjustment implies a loss in internal efficiency which decreases in individual sanctions imposed on the agent.
Keywords: D82; D86; L14; L22; K20; K21; 330; moral hazard; incentive pay; corporate crime; cartels